PROBLEMATIKA DISIPLIN PEMBELAJARAN ANTARA SISWA DAN GURU DALAM PELAKSANAAN PRAKTIK PROFESI KEGURUAN DI MA AL-MUHDI - Arrobi, Jimatul; Bahrul Ulum; Sabila Delima; Sonia; Siti Saadah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning discipline is an essential factor in determining the success of the educational process in schools. However, various disciplinary problems often occur involving both students and teachers. This study aims to analyze the problems of learning discipline between students and teachers in the implementation of Teaching Professional Practice at MA Al-Muhdi and to identify causal factors and solutions. This research uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The results show that learning discipline problems include student tardiness, lack of attention during learning, and inconsistency in enforcing classroom rules by teachers. In addition, less varied teaching methods and weak educational communication also influence discipline levels. This study contributes an integrative analysis covering both student and teacher discipline. Therefore, innovative strategies, effective communication, and consistent rule enforcement are necessary to create a conducive learning environment.